2021
DOI: 10.1016/j.xpro.2021.100413
|View full text |Cite|
|
Sign up to set email alerts
|

A Poisson generalized linear model application to disentangle the effects of various parameters on neurophysiological discharges

Abstract: Summary The protocol provides an extensive guide to apply the generalized linear model framework to neurophysiological recordings. This flexible technique can be adapted to test and quantify the contributions of many different parameters (e.g., kinematics, target position, choice, reward) on neural activity. To weight the influence of each parameter, we developed an intuitive metric (“w-value”) that can be used to build a “functional fingerprint” characteristic for each neuron. We also provide sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…V6A is particularly involved in arm-reaching movements both during the planning and execution phases (Hadjidimitrakis et al, 2014 ; Fattori et al, 2017 ; Diomedi et al, 2021 ). Recently, we found that, during foveated delayed reaching movements, spatio-temporal information about the target and task phase was distributed across the network and the population did not cluster in well-defined categories of selective units, according to the mixed selectivity scheme (Diomedi et al, 2020 ; Vaccari et al, 2021 ; see also Figure 2F ).…”
Section: The Mixed Selectivitymentioning
confidence: 90%
“…V6A is particularly involved in arm-reaching movements both during the planning and execution phases (Hadjidimitrakis et al, 2014 ; Fattori et al, 2017 ; Diomedi et al, 2021 ). Recently, we found that, during foveated delayed reaching movements, spatio-temporal information about the target and task phase was distributed across the network and the population did not cluster in well-defined categories of selective units, according to the mixed selectivity scheme (Diomedi et al, 2020 ; Vaccari et al, 2021 ; see also Figure 2F ).…”
Section: The Mixed Selectivitymentioning
confidence: 90%
“…The datasets here presented have been efficiently used in last works to functionally characterize individual neurons in the SPL, to model latent states and decode population activity 9,32 , but also to explain method of investigation 10,33 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Recent publications from our group 32,33 serve as examples of methods with which to analyse the neural data contained in these datasets, and are able to show examples of downstream processing steps. Note that to download the data files from the repository correctly, there are two options: (i) download a zip file containing data and code, directly from the official DOI webpage 14 ('Download Archive' green button); (ii) download each data file manually by navigating to the 'Data' folder of the online repository webpage (https://gin.g-node.org/SDiomedi/ SPL_single_units_reaching_task).…”
Section: Usage Notesmentioning
confidence: 99%
“…To reveal the information encoded by individual neurons, we used Poisson GLM ( glmfit ) to predict the spike count within 20 msec bins with movement profiles (behavior matrix M ) 105 .…”
Section: Pethmentioning
confidence: 99%